1344Interbirth interval and maternal anaemia in 21 sub-Saharan African countries: a multinational cross-sectional study. (2nd September 2021) - Mruts, Kalayu Brhane; Tessema, Gizachew Assefa; Gebremedhin, Amanuel Tesfay; Scott, Jane; Pereira, Gavin
Abstract: Background: Anaemia is a global public health problem, which disproportionately affects women in sub-Saharan Africa (SSA). The causes of anaemia are multifactorial, and a short interbirth interval has been identified as a potentially modifiable risk factor. However, the current evidence for the association between interbirth interval and maternal anaemia remains inconclusive. Hence, this study aimed at examining the association between the interbirth interval and maternal anaemia in SSA. Methods: We conducted a multinational cross-sectional study of interbirth interval (time between two singleton live births) and maternal anaemia for 21 SSA countries using the most recent nationally representative Demographic and Health Surveys, 2010-2017. Modified Poisson regression models were used to estimate the relative risk (RR) and 95% confidence intervals (CIs) after adjusting for confounding variables. Results: There were 81, 693 women included in the study (89.2% nonpregnant, 10.8% pregnant and 32.2% postpartum). Overall, 36.9% of women had anaemia (36.0% of non-pregnant, 44.3% pregnant, and 38.7% of postpartum women). Compared to a 24-35 months interbirth interval, maternal anaemia was not associated with short (<24 months) interbirth intervals (aRR 1.01, 95% CI; 0. 98, 1.04) or long (≥60 months) interbirth interval (aRR 1.00, 95% CI 0.96, 1. 04). Conclusions: Our finding revealed insufficient evidence that both short and long birth intervals were associated with the risk of maternal anaemia in SSA. Key messages: It is unlikely that the high prevalence of maternal anaemia in SSA can be reduced by avoiding short nor long interbirth intervals.